Growth Responses, Pigment and Stomatal Behaviour of Maize to Foliar Application of NAA (Journal of Bangladesh Academy of Sciences, 2017)
An investigation was conducted to find out the responses of two varieties of maize BHM- 7 (V1) and BHM-9 (V2) to Naphthalene acetic acid (NAA) on the growth, dry matter, pigment and stomatal behaviour. In case of V1, plant height was found to decrease due to all the treatments at all the ages except at 7 DAS due to T3 treatment. In V2, increase in plant height was recorded following T1 and T3 treatments at all the ages except at 21 DAS. In both the varieties at all the ages, maximum number of leaves per plant were obtained from T3 treatment. In case of V1 number of leaves per plant increased only due to T3 treatment in comparison to control whereas, in V2 number of leaves per plant increased following all the treatments. In case of V1, dry weight of shoot increased due to T3 treatment at 8 and 15 DAS. But in case of V2, there was increasing tendency in dry weight of shoot due to all treatments at all ages except at 8 DAS due to T2 treatment. In both the varieties dry weight of root increased due to T3 treatment at all ages. Chl. a was more than chl. b at all the stages in both the varieties and both chl. a and chl. b were recorded lowest at the flowering stage. In case of V1, amount of chl. b was remarkably higher at the tillering stage whereas, in case of V2, amount of chl. a and carotenoid were remarkably higher at the grain filling stage. In both the varieties, the amount of chl. a was found to increase and decrease due to all the treatments at all the stages. Chlorophyll b both increased and decreased in V1 and the maximum increase was due to T3 at the tillering and grain filling stages. In case of V2, chl. b increased at the tillering stage following all the treatments and maximum increase was also due to T3. However, in V1 carotenoid contents of leaf increased following all the treatments at the tillering stage and decreased following all the treatments at flowering and grain filling stages. Number of stomata increased except due to T2 in V1, whereas, number of epidermal cell decreased due to T0 and T2 in V1. Stomatal density in V2 was found relatively higher due to NAA application. It was also found that NAA increased the stomatal density with the increase of concentration except 50 ppm (T2) in V2. Stomatal index was found to decrease due to T1 inV1 and due to T0 in V2.Journal of Bangladesh Academy of Sciences, Vol. 41, No. 1, 1-9 2017